Clinical Effect and Safety of PD-1 Inhibitors plus Fruquintinib as Later-line Treatment for Metastatic Colorectal Cancer - CHEN Lulu, ZHANG Liping, LI Jingwen, DONG Wenjie, WU Xin'ai (Zhongguo quanke yixue, 2023)
Background The incidence of colorectal cancer is high, and metastatic colorectal cancer has entered a new era of targeted immunotherapy. Due to the limited choices of effective later-line treatment and the substantial reduction of physical quality caused by long-term treatment of patients who have experienced more than three lines of treatment, the choice of later-line treatment with less adverse reactions and better clinical effect needs to be further explored. Objective To observe the clinical effect and safety of fruquintinib plus programmed death receptor-1 (PD-1) inhibitors in the third-line and above treatment of mCRC. Methods The clinical data of 75 patients with metastatic colorectal cancer admitted in the First Affiliated Hospital of Zhengzhou University from June 2020 to March 2022 were collected and analyzed retrospectively. The patients were divided into the fruquintinib alone group (n=28) and the PD-1 inhibitor plus fruquintinib group (n=47). The treatment regimen was: the patients in the fuquitinib alone group took oral furoquitinib capsules at 5 mg/d once for 3 consecutive weeks with a 1-week stop in 28-day cycles, the patients in the PD-1 inhibitor plus fruquintinib group were injected intravenously with carrilizumab/sindilizumab/pabrolizumab 200 mg and treprolizumab 240 mg from the first day in 21-day cycles, and fruquintinib was used in the same way as the fruquintinib alone group. The main observation indexes were objective response rate (ORR), disease control rate (DCR), progression-free survival time (PFS) and incidence of adverse reactions in the two groups. Results As of the last follow-up (2022-05-31), the ORR of the fruquintinib alone group and the PD-1 inhibitor plus fruquintinib group were 7.1% and 14.9%, the DCR of the fruquintinib alone group and the PD-1 inhibitor plus fruquintinib group were 67.9% and 89.4%, the DCR of patients in the PD-1 inhibitor plus fruquintinib group was significantly higher than that in the furoquinitinib alone group (χ2=5.345, P=0.021). The median PFS of the PD-1 inhibitor plus fruquintinib group and fruquintinib alone group were 6.4 months (IQR: 4.0-13.1) and 4.5 months (IQR: 2.9-8.2) ; there was significant difference in PFS between the two groups (χ2=5.504, P=0.019). Most of the adverse reactions during the treatment of the two groups were grade 1-2. The incidence of hypothyroidism in the PD-1 inhibitor plus fruquintinib group was significantly higher than that in the fruquintinib alone group (P<0.05). In addition, there was no significant difference in the incidence of other adverse reactions between the two groups (P>0.05) . Conclusion Compared with fruquintinib alone, PD-1 inhibitor plus fruquintinib has prolonged survival time and reduced incidence of severe adverse reactions in patients with metastatic colorectal cancer, making it an effective and safe treatment.